Pemberdayaan Lingkungan Masyarakat Melalui Sosialisasi Hidroponik System Wick (Sumbu) Di Desa Gading Permai Kec. Kampar Kiri Hilir, Kab. Kampar, Riau - Alif Hadi Ariansyah; Fathra Annis Nauli; Jenni Nurika Wisyana Nasution (Pusat Riset dan Inovasi Nasional, 2023)
The socialization of hydroponics to the village community is an effort to develop the independence and welfare of the community by improving knowledge, attitudes, skills, Hydroponics is a cultivati Wick hydroponics is a simple hydroponic method that uses a wick as a link between nutrients and the roots of the growing media. This activity was carried out in Gading Permai Village, Kampar Kiri Hilir District, Kampar, Riau. This activity began with a theoretical and practical explanation with pakcoy mustard plants as an example, the practice carried out starting from seed sowing, wick system hydroponic installation, transplanting and continued with a discussion session. The results of this activity are that the Gading Permai village community knows hydroponics in general, wick system hydroponics, hydroponic plant maintenance, handing over hydroponics to the Gading Permai village community so that they can continue to care for and continue hydroponic cultivation. This activity adds to the knowledge and insight of the Gading Permai village community about hydroponics and can spread and teach the knowledge that has been given to fellow communities.